2018
DOI: 10.1155/2018/7980413
|View full text |Cite
|
Sign up to set email alerts
|

Ingesting Self-Grown Produce and Seropositivity for Hepatitis E in the United States

Abstract: Background Hepatitis E virus (HEV) is a major cause of hepatitis in developing and industrialized countries worldwide. The modes of HEV transmission in industrialized countries, including the United States, remain largely unknown. This study is aimed at evaluating the association between HEV seropositivity and consumption of self-grown foods in the United States. Methods Cross-sectional data was extracted from the 2009–2012 National Health and Nutrition Examination Survey (NHANES). Data from the dietary interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the general population, it was found that females had a higher prevalence than males (OR 1.2 (1.06–1.38)) [ 50 ], and those young females (6–39 years) were found to have higher HEV seropositivity compared to males (OR 1.44 (1.03–2.02)) [ 71 ]. In contrast, one study found that males had a higher anti-HEV IgG prevalence rate than females [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the general population, it was found that females had a higher prevalence than males (OR 1.2 (1.06–1.38)) [ 50 ], and those young females (6–39 years) were found to have higher HEV seropositivity compared to males (OR 1.44 (1.03–2.02)) [ 71 ]. In contrast, one study found that males had a higher anti-HEV IgG prevalence rate than females [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Blood of HEV RNA-positive pigs potentially can contaminate slaughterhouses' supply chains, making it a key source of infection control[ 24 ]. A recent study suggested consuming self-grown food as another possible source for zoonotic HEV infection[ 25 ].…”
Section: Hev Transmissionmentioning
confidence: 99%
“…Furthermore, ingesting self-grown food has been hypothesized to be another risk factor for seropositivity in the United States [ 20 ]. Dietary intake may play a role in the causal pathway to HEV infection in this study.…”
Section: Discussionmentioning
confidence: 99%